TOTAL FENOLIK,FLAVONOID SERTA AKTIVITAS ANTIOKSIDAN EKSTRAK n-HEKSANA, DIKLOROMETAN DAN METANOL Amaranthus spinosus L EM5-BAWANG PUTIH - Yondra Arif D; Christine Jose; Hilwan Yuda Teruna (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The objective of this study was to analyze the total phenolics, total flavonoids, andantioxidant activities of Amaranthus spinosus L leaves. During cultivation, these plantswere treated with 2 treatments, biocontrol Effective Microorganism 5 (EM5) garlic andcontrol (water). The A. spinosus L leaves were dried using freeze dryer and extracted bydissolving n-hexane, dicloromethane (DCM) and methanol. The results showed thatA.spinosus L leaves treated with biocontrol had the highest total phenolic, totalflavonoid and antioxidant activity content compare to the control. The total phenolic,total flavonoid, 2,2 diphenyl-1-picrylhydrazyl (DPPH) and Nitric Oxide (NO) radicalscavenging were the highest on DCM extract with each value of 74,656 mg Gallic AcidEquivalent (GAE)/g of dry weight (DW), 22,337 mg Catechin Equivalent (CE)/g DW,0,373 mg/mL and 0,025 mg/mL. n-Hexane extract had the highest antioxidant activityon Ferric Thiocyanate ( FTC) test (27,615 %), meanwhile methanol extract indicated thehighest antioxidant activity on FRAP test (1,022 mmol Fe +2 /g DW). From this study,it can be concluded that A. spinosus L leaves with biocontrol EffectiveMicroorganism 5 (EM5) garlic can increase the phenolic, flavonoids and antioxidantactivitiy contents of A. spinosus L plant.